The Concreteness of The Invisible - Tony Duncan; Bryan Zimmer; Todd Devin Powers; Gary L. Holler; Bradley Skaggs; Bruce A. Johnson (Oz, 1991)
The project commenced with the assumption that the manifested physical form of city (the one which we verify through common perception as objectivization of the idea of city) is a deception.